Implementation of Dunaliella tertiolecta and Desmodesmus communis in a photobioreactor prototype for treatment of wastewater in a recirculating aquaculture system - Kathleen P. Nolan; Jordan Roszell; Robert H. Hanner; Andreas Heyland (Current Research in Biotechnology)
Inline photobioreactors (PBRs) are a promising tool for nutrient removal from aquacultural wastewater and production of valuable algal biomass, yet few PBR systems have been rigorously tested. Optimization of algal growth screening across species and strains of interest under specific water conditions is crucial but time-consuming, limiting PBR implementation. Here, we developed a high-throughput screening system to efficiently test algal growth under various nutrient treatments, with the goal of informing implementation in a PBR designed for wastewater treatment in recirculating aquaculture systems (RAS). We assessed growth of the marine alga Dunaliella tertiolecta and the freshwater alga Desmodesmus communis under a matrix of inorganic nitrogen (N) treatments in 96-well plates. We then tested ammonium transfer within a prototype PBR for RAS wastewater treatment and evaluated the batch growth response of D. tertiolecta to ammonium treatments in the PBR. Both species grew on the provided inorganic N sources, showing significant differences in response to N treatments due to species-driven variations in nitrogen uptake and storage mechanisms. D. tertiolecta thrived when grown individually on either nitrate or ammonium, while D. communis favored a combination of N sources. D. tertiolecta showed a 5.4% higher growth rate in nitrate than ammonium. Both species grew in nutrient-free controls, suggesting potential use of internal nutrient reserves. D. tertiolecta grew within the PBR, serving as proof-of-concept for algal cultivation in the prototype. This study supports PBR technology for enhancing food production systems and protecting food security through RAS wastewater treatment.